PERANCANGAN MOBILE APPS PLATFORM UNTUK PEMENUHAN KEBUTUHAN HEWAN PELIHARAAN - Irlanda Putri, Sheila; Yudiarti, Diena; Lukito, Wahyu (Telkom University, 2024)
The increasing use of technology today has brought about positive changes invarious fields. The ease of getting daily needs efficiently with technology has a significant impact on the fulfillment of daily needs, especially for pets. This research aims to describethe design of user interfaces related to pet fulfillment applications. The results of this study are expected to provide a good solution for pet owners to meet the needs of their pets.This research is a qualitative research in the form of literature study, observation and interviews. This design uses the Design Thinking approach method. The data obtained inthis study were then further analyzed using comparison matrix analysis and visual analysis. Then, the research focuses on the subject of discussion around User Interfacedesign, User Experience and Application Design. The explanation related to this is useful to understand how the application design will work to realize the main purpose of theapplication, namely the fulfillment of effective and efficient pet needs. It is hoped that this application will be the right solution to all existing problems. Keywords: Design thinking, mobile apps, User Interface, User Experience, pets